Challenging Contextual Factors in University-Community Partnerships - Beth Archer-Kuhn; Jill Grant (The University of Alabama, 2022)
In this paper, we discuss a community-university partnership struck with the intention of carrying out data analysis for the purposes of service planning and policy implementation that led us to find ourselves in the middle of significant stakeholder conflict. The purpose of this paper is to reflect upon and illuminate the challenges affecting this partnership revealing the impactful contextual factors through a process of reflection and consultation with the research literature. The significant benefits to ensuring a participatory process for both the university faculty and community agency have been cited in the research literature; yet the very real challenges inherent in such a process are less well documented. This example of civic engagement is presented through a partnership between a university faculty member and a children's mental health center. An analysis of the partnership within the project is presented to illuminate power and contextual factors that can influence partnership projects. As part of the contextual factors, we review the process of partnerships both through the literature and analysis of our project. Suarez-Balczar, Harper, and Lewis' (2005) model for developing university community partnerships provides guidance while questions for considering the scope are recommended and suggestions for future partnerships including increasing stakeholder breadth are identified.